Gastric Emptying and Distal Gastrectomy Independently Enhance Postprandial Glucagon-Like Peptide-1 Release After a Mixed Meal and Improve Glycemic Control in Subjects Having Undergone Pancreaticoduodenectomy. Issue 7 (August 2019) - Steiner, Emanuel; Breuer, Robert; Kazianka, Lukas; Wewalka, Marlene; Stimpfl, Thomas; Reiter, Birgit; Holst, Jens Juul; Miholic, Johannes
Abstract : Objectives: New-onset diabetes frequently resolves after pancreaticoduodenectomy (PD). Glucagon-like peptide-1 (GLP-1) conceivably is involved as its release is enhanced by rapid gastric emptying and distal bowel exposure to nutrients. We aimed at studying factors associated with GLP-1 release after PD. Methods: Fifteen PD subjects with distal gastrectomy (Whipple) and 15 with pylorus preservation were evaluated. A test meal containing 1 g paracetamol to measure gastric emptying was ingested. Blood for the measurement of paracetamol, glucose, insulin, and GLP-1 was drawn at baseline and 10, 20, 30, 60, 90, 120, 150, and 180 minutes thereafter. The Matsuda index of insulin sensitivity was calculated. Results: In univariate analysis, gastric emptying correlated with GLP-1. Glucagon-like peptide-1 responses to the modes of operation did not differ. Multiple regression analysis confirmed gastric emptying and Whipple versus pylorus-preserving pancreaticoduodenectomy as independent predictors of GLP-1 release. The Matsuda index of insulin sensitivity correlated with GLP-1 concentrations and inversely with body mass index. Patients after Whipple procedure revealed lower glycated hemoglobin as compared with pylorus-preserving pancreaticoduodenectomy. Conclusions: Following PD, the postprandial GLP-1 release seems to be enhanced by rapid gastric emptying and to improve insulin sensitivity. Partial gastrectomy versus pylorus preservation enhanced the release of GLP-1, conceivably because of greater distal bowel exposure to undigested nutrients.